Pemberdayaan Masyarakat Nelayan Melalui Pelatihan Perawatan Berkala Mesin Kapal di Desa Galesong Kota Kabupaten Takalar - Muhammad Rusydi Alwi; Zulkifli A Yusuf; Baharuddin .; Syerly Klara; Surya Hariyanto; Andi Husni Sitepu; Haryanti Rivai; Muhammad Iqbal Nikmatullah; Balqis Shintarahayu (Faculty of Engineering UNHAS, 2022)
The “Karya Bersama” Fisherman Group in Galesong Village, Galesong District, Takalar Regency as partners in this activity using an outboard engine as a fiberglass boat propulsion engine in fishing activities. In the initial observation, information was found that the service life of their boat engine was very low, which was about 3 years because the engine was often failure. The causes of engine failure are the lack of fishermen’s knowledge on how to run the engine properly and engine maintenance techniques. This community service aims to increase the knowledge of partners in boat engine maintenance techniques. The expected benefit of this activity is to reduce the number of engine breakdowns and reduce operational costs, especially the cost of repairing boat engines. The method of this service activity is counseling by providing material about the general description of ship propulsion engines, types of engine damage, and periodic maintenance techniques on boat engines. Evaluation of the level of knowledge of participants in receiving the transfer of science and technology is carried out using the pre-test method at the beginning of the activity and the post-test conducted at the end of the activity. The results of the activity showed that 90% of the 10 participants had good knowledge of boat engine periodic maintenance techniques and were able to carry out engine maintenance activities correctly.